DOZ047.49: Tracheoscopic findings and their impact on respiratory symptoms in children with esophageal atresia. (24th June 2019) - Janina, F; Josef, H; Grigore, C; Martin, D
Abstract : Introduction: Esophageal atresia is often accompanied by tracheobronchial malformations leading to stridor, recurrent bronchitis and occasionally to life threatening obstructive apnea after surgical repair. The aim of this study was to identify the presence of tracheomalacia in patients with esophageal atresia (EA) and tracheo-esophageal fistula (TEF) pre- and postoperatively and to find endoscopic correlates leading to clinical airway symptoms. Methods: In a cohort of 362 patients with EA-TEF who underwent 595 tracheoscopies at the Children's Hospital of Cologne between January 1983 and December 2002, impaired tracheal lumen, localization of TEF, tracheal pulsations and corresponding clinical symptoms were retrospectively analyzed. Results: The incidence of tracheomalacia was higher in patients with EA and TEF (Gross B, C, D) compared to patients with EA alone (Gross A) and average tracheal collapse does not significantly change before and after surgical repair of the esophagus in all types. Patients with cyanosis while eating and obstructive apnea presented with an average tracheal collapse of 89%. Presence of respiratory symptoms like cough, stridor or bronchitis was not associated with a higher grade of tracheal collapse compared to patients without any airway symptoms (average tracheal collapse of 37% in symptomatic patients vs. 33% in non-symptomatic patients). Conclusion: Tracheomalacia tends to be present independently of surgical procedure. Tracheomalacia should be measured by tracheoscopy (in % of tracheal collapse). Patients with a tracheal collapse of > 80%, a ventral pulsation and obstructive apnea or cyanosis in combination, are at risk for life threatening situations.